On the Possibilities of Existence of Photosynthetic Life around Alpha Centauri B - Estrada-Rodriguez, G.; González-Noa, A.; Cardenas, R. (Revista Cubana de Física, 2019)
We start with a brief description of the Alpha Centauri system and its main characteristics. Afterwards, we carry out calculations of several habitability metrics, such as the Π biological productivity and photosynthesis rates, in the oceans of the hypothetical exoplanets orbiting around Alpha Centauri B. By including a function of the temperature in a photosynthetic model, we describe the behavior of the metrics mentioned above for organisms with prokaryotic and eukaryotic cells that could potentially live in these exoplanets.